2012
DOI: 10.4103/2152-7806.103872
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality conferences: Their educational role and why we should be there

Abstract: Background:This article examines the value of morbidity and mortality (M&M) conferences, and the multiple factors that contribute to their efficacy. Physicians’ morbidity and mortality conferences (M&MCs) focus on education by reviewing individual adverse events (AE), M&M. Alternatively, Quality Assurance (QA) conferences better examine system-wide issues (e.g., the role institutions play) in attaining or maintaining acceptable levels of patient care. Other issues examined in this review include: whether prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
1
24
0
3
Order By: Relevance
“…Barriers that are consistently identified across reviews include a focus on individuals rather than systems and variation in the structure and format of M&M meetings. As noted in prior reviews, our review also found limited evidence favouring a particular format or structure of M&M meetings. In light of the limited evidence demonstrating the superiority of one particular format over another, our review identified a set of enabling and inhibiting factors that can be applied to local settings.…”
Section: Discussionmentioning
confidence: 98%
“…Barriers that are consistently identified across reviews include a focus on individuals rather than systems and variation in the structure and format of M&M meetings. As noted in prior reviews, our review also found limited evidence favouring a particular format or structure of M&M meetings. In light of the limited evidence demonstrating the superiority of one particular format over another, our review identified a set of enabling and inhibiting factors that can be applied to local settings.…”
Section: Discussionmentioning
confidence: 98%
“…The inconsistencies in MMR formats among the various veterinary surgery programs is a weakness of veterinary MMR identified in this study, especially compared with human surgery training programs. Standardization of the review process and prospective, standardized data collection have been found to result in several benefits in human medicine, improving the accountability and quality of mortality data along with the identification of quality of care issues and supporting patient care quality improvement efforts, particularly for programs targeting the surgical patient . Standardizing the format of MMR has also been shown to improve residents' understanding of medical concepts presented in rounds .…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [30][31][32] these conferences are arranged once a month as a departmental learning conferences where all the important cases with mortality and morbidity issues are collected and discussed. The candidate is asked to prepare the case and look at the current evidence to support the management done or best management which should have been given.…”
Section: Mortality and Morbidity Conferencementioning
confidence: 99%